3x-4y+2z+5x+2y-3z=

Simple and best practice solution for 3x-4y+2z+5x+2y-3z= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x-4y+2z+5x+2y-3z= equation:


Simplifying
3x + -4y + 2z + 5x + 2y + -3z = 0

Reorder the terms:
3x + 5x + -4y + 2y + 2z + -3z = 0

Combine like terms: 3x + 5x = 8x
8x + -4y + 2y + 2z + -3z = 0

Combine like terms: -4y + 2y = -2y
8x + -2y + 2z + -3z = 0

Combine like terms: 2z + -3z = -1z
8x + -2y + -1z = 0

Solving
8x + -2y + -1z = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '2y' to each side of the equation.
8x + -2y + 2y + -1z = 0 + 2y

Combine like terms: -2y + 2y = 0
8x + 0 + -1z = 0 + 2y
8x + -1z = 0 + 2y
Remove the zero:
8x + -1z = 2y

Add 'z' to each side of the equation.
8x + -1z + z = 2y + z

Combine like terms: -1z + z = 0
8x + 0 = 2y + z
8x = 2y + z

Divide each side by '8'.
x = 0.25y + 0.125z

Simplifying
x = 0.25y + 0.125z

See similar equations:

| R(2)=96 | | 2cd*cd= | | 4x+3+8-3x=-2x+6x-2 | | 30x+4=244 | | 3p^2+10=310 | | 4hk*5st= | | 3mn*9m= | | 2,5/x=8/3 | | 2x+3y+0.1z=100 | | 7x-3y+2x-10y= | | 4x-24=3x+36 | | -4fgh^2*(-2gh)= | | 6w^2+9w+2=0 | | 9=2r+r | | .33x-2=.25x+3 | | 3pq*2pr= | | 5y-11=24whatisy | | 5y-11=24wgatisy | | 2(x+1)+x=7 | | cos(36+x)+cos(x)=0 | | cosx(36+x)+cos(x)=0 | | 0.5D^2+1.5D+1=0 | | tan*x=0.625 | | 4(3x+6)=9 | | 2/x-1/7=7/x | | 10x-3=2x+1 | | sin(45)=x/18 | | x+8=x*(x-6) | | 81x^3+1=0 | | (p^-4b)/(12c^2) | | 2(3x-1)-(x-2)=5 | | (p^-4b)/12c^-2 |

Equations solver categories